A Transient Assay to Evaluate the Expression of Polyhydroxybutyrate Genes Regulated by Oil Palm Mesocarp-Specific Promoter - Omidvar, Vahid; Abdullah, Siti Nor Akmar; Mahmood, Maziah; Abdul Aziz, Maheran (Springer Verlag, 2008)
The promoter of the oil palm metallothionein-like gene (MT3-A) demonstrated mesocarp-specific activity in functional analysis using transient expression assay of reporter gene in bombarded oil palm tissue slices. In order to investigate the tissue-specific expression of polyhydroxybutyrate (PHB) biosynthetic pathway genes, a multi-gene construct carrying PHB genes fused to the oil palm MT3-A promoter was co-transferred with a construct carrying GFP reporter gene using microprojectile bombardment targeting the mesocarp and leaf tissues of the oil palm. Transcriptional analysis using RT-PCR revealed successful transcription of all the three phbA, phbB, and phbC genes in transiently transformed mesocarp but not in transiently transformed leaf tissues. Furthermore, all the three expected sizes of PHB-encoded protein products were only detected in transiently transformed mesocarp tissues on a silver stained polyacrylamide gel. Western blot analysis using polyclonal antibody specific for phbB product confirmed successful translation of phbB mRNA transcript into protein product. This study provided valuable information, supporting the future engineering of PHB-producing transgenic palms.